1984
DOI: 10.1111/j.1365-3083.1984.tb01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative Responses of Spleen Cells of Inbred Rat Strains to Mycoplasma arthritidis Mitogen

Abstract: A potent mitogen for T lymphocytes of various species has recently been isolated from the supernatant of cultured Mycoplasma arthritidis organisms (MAS). In the mouse, reactivity to this mitogen has been observed to be controlled by the I-E subregion of the major histocompatibility complex. We have analysed the responses of spleen cells from several inbred rat strains covering practically all known haplotypes of the major histocompatibility complex of the rat (RT1). Unlike in the mouse, all of these responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Based on relative changes in transcript levels from nonstimulated to stimulated cells, it appears that mVp6, mVp8.2, and mV,5.1 are the strongest engaged by MAM, followed by rnV9.l and mVp8.3. To determine whether rats, which have an overall V , genomic composition almost identical to that of mice (29), respond to MAM in a similar manner, we assessed the responses of spleen cells from a strain of rats known to be a high responder to this mitogen (Lewis rats) (10,30). As indicated in Figure 1, transcript levels for rat V , (rV& 5.1, 6, 8.1, and 8.2 were strongly enriched in these cultures but rVp8.3, in contrast to mV,8.3, was not engaged.…”
Section: Methodsmentioning
confidence: 99%
“…Based on relative changes in transcript levels from nonstimulated to stimulated cells, it appears that mVp6, mVp8.2, and mV,5.1 are the strongest engaged by MAM, followed by rnV9.l and mVp8.3. To determine whether rats, which have an overall V , genomic composition almost identical to that of mice (29), respond to MAM in a similar manner, we assessed the responses of spleen cells from a strain of rats known to be a high responder to this mitogen (Lewis rats) (10,30). As indicated in Figure 1, transcript levels for rat V , (rV& 5.1, 6, 8.1, and 8.2 were strongly enriched in these cultures but rVp8.3, in contrast to mV,8.3, was not engaged.…”
Section: Methodsmentioning
confidence: 99%
“…The tnitogenic activity was found as a soluble and filtrable entity in the M. arthritidis culture supernatants. The precise identity of M. arthritidis soluble mitogen (MAS) is still unclear (Moritz et al 1984); however, it has been reported that a small basic protein of 15000 Da (Atkin et al 1986) resembles rheumatoid arthritis in humans (Washburn 1987). Further work then revealed that the ability of T lymphocytes to respond to MAS not only requires expression of the Ea chain of the I-E-encoded molecule, but also depends upon non-MHC gene(s) ).…”
Section: Mycoplasma Effects On T Lymphocytes In Vitromentioning
confidence: 99%